The static and dynamic benefits of migration and remittances in Nicaragua - Lykke E. Andersen; Bent Jesper Christensen (Institute for Advanced Development Studies (INESAD), 2009)
This paper utilizes a unique three-wave panel of household data from Nicaragua, which allows a thorough exploration of the relationships between migration, remittances and household consumption. The paper distinguishes between the effects of emigration and the impacts of remittances received. There is a self-selection bias in the decision to send a migrant, as well as in the decision to receive remittances. To adequately correct for these selection biases, we develop a bivariate selection correction procedure. Perhaps surprisingly, the results show that households do not benefit (in terms of higher consumption growth) from receiving remittances, but rather from having migrants abroad. This suggests that not only money are remitted from abroad, but also something more subtle, which could be business ideas, belief systems, aspirations, patterns of social interaction, and other intangibles, which have been dubbed social remittances.
Keywords: F35; 330; Migration; Remittances; Social Remittances; Nicaragua; Bivariate Selection Correction